2005
DOI: 10.1093/petrology/egi029
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Gradations among Primary Carbonatitic, Kimberlitic, Melilititic, Basaltic, Picritic, and Komatiitic Melts in Equilibrium with Garnet Lherzolite at 3–8 GPa

Abstract: Multianvil melting experiments in the system CaO-MgO-Al 2 O 3-SiO 2-CO 2 (CMAS-CO 2) at 3-8 GPa, 1340-1800 C, involving the garnet lherzolite phase assemblage in equilibrium with CO 2-bearing melts, yield continuous gradations in melt composition between carbonatite, kimberlite, melilitite, komatiite, picrite, and basalt melts. The phase relations encompass a divariant surface in P-T space. Comparison of the carbonatitic melts produced at the low-temperature side of this surface with naturally occurring carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
203
3
12

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 329 publications
(240 citation statements)
references
References 37 publications
22
203
3
12
Order By: Relevance
“…The same coordination for T 1 and T 2 cations favors the intermixing of the cations of these two sites and hence differences in local coordination around these sites have been observed in natural melilite-type and related structures. 7,10 The local distortion in the tetrahedral net and the A-site coordination plays a crucial role in governing the topology of the tetrahedral units and final symmetry of the structure of such complex compounds. 5,9 Furthermore, local distortions in the cation polyhedra resulting from slightly different compositions are strongly reflected on materials properties; in particular, on the optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The same coordination for T 1 and T 2 cations favors the intermixing of the cations of these two sites and hence differences in local coordination around these sites have been observed in natural melilite-type and related structures. 7,10 The local distortion in the tetrahedral net and the A-site coordination plays a crucial role in governing the topology of the tetrahedral units and final symmetry of the structure of such complex compounds. 5,9 Furthermore, local distortions in the cation polyhedra resulting from slightly different compositions are strongly reflected on materials properties; in particular, on the optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Red triangles indicate recent and active volcanoes. Dalton and Presnall (1998), and Gudfinnsson and Presnall (2005), and peridotite -CO 2 (2.5 wt %) from . Dry peridotite solidus in the CMAS system is from .…”
mentioning
confidence: 99%
“…Similarly Brey (1978) and Keshav & Gudfinnsson (2004) concluded that melilitites and nephelinites are partial melts of carbonated lherzolites at 3 GPa (or higher). In the experiments of Gudfinnsson & Presnall (2005), the melilitite melts resembling natural me- -data for melilite olivine nephelinite. Gudfinnsson & Presnall (2005) our analytical data plot mostly to or close to a field for melilites near the 3 GPa isobar, yet some are located outside the field at considerably lower pressures.…”
Section: Melilitic Magma Generation and Its Sourcesmentioning
confidence: 89%
“…In the experiments of Gudfinnsson & Presnall (2005), the melilitite melts resembling natural me- -data for melilite olivine nephelinite. Gudfinnsson & Presnall (2005) our analytical data plot mostly to or close to a field for melilites near the 3 GPa isobar, yet some are located outside the field at considerably lower pressures. Falloon & Green (1990) estimated the formation of the olivine melilitite magma in equilibrium with garnet-phlogopite lherzolite within the dolomite stability field as 1020 °C at pressures > 2.5 GPa.…”
Section: Melilitic Magma Generation and Its Sourcesmentioning
confidence: 89%